2015
DOI: 10.1186/s13058-015-0518-y
|View full text |Cite
|
Sign up to set email alerts
|

Mammary gland tumor promotion by chronic administration of IGF1 and the insulin analogue AspB10 in the p53R270H/+WAPCre mouse model

Abstract: IntroductionInsulin analogues are structurally modified molecules with altered pharmaco-kinetic and -dynamic properties compared to regular human insulin used by diabetic patients. While these compounds are tested for undesired mitogenic effects, an epidemiological discussion is ongoing regarding an association between insulin analogue therapy and increased cancer incidence, including breast cancer. Standard in vivo rodent carcinogenesis assays do not pick up this possible increased carcinogenic potential.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 38 publications
0
29
0
1
Order By: Relevance
“…Our findings are consistent with a previous mouse study that examined the latency time for mammary tumour development in a p53 mutant mouse model. In that study, AspB10 insulin and IGF-1 significantly decreased tumour latency compared with vehicle, but tumor latency was comparable between NPH insulin, glargine and vehicle [24]. Insulin glargine has been shown in vitro to have growth-promoting effects on specific cancer cell lines that express high levels of the IGF-1R [6, 9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with a previous mouse study that examined the latency time for mammary tumour development in a p53 mutant mouse model. In that study, AspB10 insulin and IGF-1 significantly decreased tumour latency compared with vehicle, but tumor latency was comparable between NPH insulin, glargine and vehicle [24]. Insulin glargine has been shown in vitro to have growth-promoting effects on specific cancer cell lines that express high levels of the IGF-1R [6, 9].…”
Section: Discussionmentioning
confidence: 99%
“…Insulin glargine has been shown in vitro to have growth-promoting effects on specific cancer cell lines that express high levels of the IGF-1R [6, 9]. The lack of mitogenicity of insulin glargine in vivo, however, was believed to be due to the rapid metabolism of glargine to its M1 metabolite [7, 9, 24]. Even after administration of high doses of insulin glargine, we found that glargine was metabolised into the M1 metabolite and did not lead to tumour progression.…”
Section: Discussionmentioning
confidence: 99%
“…For instance B10Asp, a single amino-acid-substituted insulin analog, has increased affinity for both IR and IGF-1R and a longer residence on the receptor. These characteristics are associated with increased occurrence of mammary tumors in female rats [77][78][79].…”
Section: Insulin Analogsmentioning
confidence: 99%
“…In vitro studies have shown that the PI3K signaling pathway [36][37][38][39] and the MAPK pathway [36,37] are significantly upregulated after stimulation of insulin analogues compared to human insulin. In mammary gland tumors of mice, expression of IR, IGF1R and p-AKT was significantly higher in insulin or insulin analogues-treated compared to vehicle-treated mice, while expression of p-ERK was only increased among tumors of mice treated with insulin analogues [21]. Our results suggest that treatment with insulin and insulin analogues increases signaling via mTOR.…”
Section: Discussionmentioning
confidence: 53%
“…In vitro, insulin analogue stimulation increases proliferation of breast cancer cells due to enhanced IGF1R (and INSR) signaling, while exposure to human insulin showed low mitogenic potential [20]. Chronic treatment with insulin-like compounds (IGF1, insulin AspB10) with strong binding affinity towards the IGF1R, decreased the tumor latency time and showed increased MAPK-ERK signaling in a mammary gland mouse model, while insulin glargine and human insulin treatment did not significantly decrease the time for tumor development compared to the vehicle-treated mice [21].…”
Section: Introductionmentioning
confidence: 99%